Theory of two-dimensional photonic crystals with lamellar cylindrical pores - Glushko, A.E.; Glushko, E.Ya.; Karachevtseva, L.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Theoretical investigation of 2D photonic crystals containing intermediate layers on the surface of cylindrical pores is performed within the framework of the plane-wave model. We have analyzed how the third medium introduction influences on the absolute bandgap formation in the triangular lattice photonic structure. We have obtained the dependences of the bandgap width and position on the additional interlayer thickness d and its dielectric constant εi. The new concept of photonic contrast is introduced in order to describe the bandgap formation conditions. We conclude that addition of the surface layer decreases the photonic band gap width of the examined system.